Assessment of school readiness and the importance of executive functions for learning - Rachel Mocelin Dias Coelho; Sandra Josefina Ferraz Ellero Grisi; Alexandra Valéria Maria Brentani; Ana Paula Scoleze Ferrer (Sociedade de Pediatria de São Paulo, 2023)
ABSTRACT Objective: Considering the importance of the beginning of the academic trajectory for children to reach their full development, this work aims to evaluate the school readiness of preschool-age children and identify which factors influence these results, in order to contribute to the proposition of strategies that allow improving the teaching-learning process and child development. Methods: This is a cross-sectional, descriptive and analytical study with 443 preschool children belonging to the West Region Cohort (ROC Cohort), from the public school system of the city of São Paulo. School readiness was assessed by the International Development and Early Learning Assessment (IDELA) tool. Non-parametric techniques were used for the correlation analysis between IDELA scores and sociodemographic and socioeconomic conditions: Spearman's parametric correlation, Mann-Whitney and Kruskal-Wallis tests. Results: The children's mean age was 69 months (standard deviation - SD=2.8; ranging from 55 to 72 months) and most of them came from families with low socioeconomic level. Most children showed adequate readiness in the overall score (65%) and in most domains, except for emergent literacy, in which most (56.9%) were classified as "emergent". The highest percentage of insufficiency was identified in executive functions (4.1%), which showed a correlation only with the caregiver's education. Conclusions: Children had adequate school readiness scores, except for emergent literacy, but the insufficiency in executive functions may compromise the future schooling of these children. Thus, pedagogical proposals should consider these aspects for learning and pediatricians need to reinforce the habit of reading and playing games to stimulate child development.